A partitioned solution approach for the simulation of the dynamic behaviour of flexible marine propellers. Issue 1 (2nd January 2020) - Radtke, L.; Lampe, T.; Abdel-Maksoud, M.; Düster, A.
ABSTRACT: Modern designs of ship-propellers make use of novel materials such as composites, which may show a much lower stiffness than classical material. In order to accurately predict the hydrodynamic characteristics of these propellers in real operating conditions, the structural deformation must be accounted for, which leads to a fluid-structure interaction problem. In the present paper, a partitioned solution approach for such a strongly coupled two-field problem is presented. Owing to the separate modelling of the fluid and the structural problem in such approaches, specialised numerical methods can be applied on either side. Thanks to their superior convergence properties, we use high-order finite elements to discretise the structural problem. On the fluid side, a boundary element method, which is specifically designed to simulate the hydrodynamic behaviour of ship propellers is employed. In order to stabilise the solution procedure, different coupling algorithms and convergence acceleration methods are investigated.